Cyclic behavior of substandard reinforced concrete beam-column joints with plain bars - Fernandes, C. (2013)
An experimental investigation aimed at assessing the cyclic behavior of substandard interior beam-column joints built with plain reinforcing bars is described in this paper. Five specimens with plain reinforcing bars and one with deformed bars were tested under reversed cyclic loading. The influence of bond properties, displacement history, column axial load, and amount of reinforcement was investigated. A comparison was established in terms of maximum strength, damage, energy dissipation, ductility, displacement components, and rotation capacity. Better bond properties led to a more spread damage distribution and larger energy dissipation. Higher column axial load resulted in larger lateral strength and energy dissipation. A larger amount of longitudinal and transverse reinforcement did not necessarily lead to enhanced behavior. The test results contribute to the characterization of the cyclic behavior of beam-column joints with plain bars and can be used to calibrate numerical models for the simulation of this type of element.